2020
DOI: 10.1140/epja/s10050-019-00010-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 139La(p,x) cross sections from 35–60 MeV by stacked-target activation

Abstract: A stacked-target of natural lanthanum foils (99.9119% 139 La) was irradiated using a 60 MeV proton beam at the LBNL 88-Inch Cyclotron. 139 La(p,x) cross sections are reported between 35-60 MeV for nine product radionuclides. The primary motivation for this measurement was the need to quantify the production of 134 Ce. As a positron-emitting analogue of the promising medical radionuclide 225 Ac, 134 Ce is desirable for in vivo applications of bio-distribution assays for this emerging radio-pharmaceutical. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
(66 reference statements)
1
22
0
Order By: Relevance
“…A possible way to improve this is to use the stacked target activation method (e.g. Morrell et al 2020) for measurements of cross sections at energies lower than the provided beam energy. If there are γ activity setups available, simultaneous measurements of cross sections at a series energies would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…A possible way to improve this is to use the stacked target activation method (e.g. Morrell et al 2020) for measurements of cross sections at energies lower than the provided beam energy. If there are γ activity setups available, simultaneous measurements of cross sections at a series energies would be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It may be mentioned that the population branching of the isomeric and ground state, σ m,g /(σ m + σ g ), in 137 Ce m,g was 78(4) and 22(4)%, respectively, with insignificant variation in the incident proton beam energy range of 36-56 MeV, deduced using the cross section data σ from Ref. [42]. In the 139 La(p, 3n) 137 Ce m,g reaction, the high-spin (11/2 − ) isomeric state was preferentially populated compared to the low-spin (3/2 − ) ground state due to higher angular momentum of the compound nucleus carried by the high-energy protons.…”
Section: B Data Acquisition and Analysismentioning
confidence: 99%
“…Here we describe the irradiations and measurements in detail relevant to this work, i.e., for relative γ -ray intensities of the parent and daughter radioisotopes in transient equilibrium. Cross section data of the 139 La(p, x) reactions have been published by Morrell et al [42] and data of the 86 Sr(p, x) reactions will be published in upcoming articles.…”
Section: Measurementsmentioning
confidence: 99%
“…The continued rise of nuclear medicine to study physiological processes, diagnose, and treat diseases requires improved production routes for existing radionuclides, as well as new production pathways for entirely novel radioisotopes [1]. The implementation of these new methodologies or products in nuclear medicine relies on accurate and precise nuclear reaction cross section data in order to properly inform and optimize large scale creation for clinical use [2][3][4][5][6][7]. A primary component in obtaining these data is a suitable reaction monitor, defined as a long-lived radionuclide with a well-known cross section as a function of incident beam energy, that can accurately describe beam properties during a production irradiation [2,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the (p,4n) channel, production cross sections were extracted for 22 additional reaction products. This extensive body of data forms a valuable tool to study nuclear reaction modeling codes and assess the predictive capabilities for proton reactions on spherical nuclei up to 200 MeV [6,[11][12][13][14][15], which have been studied less than neutron-induced reactions [16]. It was demonstrated that default modeling predictions from TALYS, CoH, EMPIRE, and ALICE codes failed to reproduce the measured niobium data and required modifications to improve [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%